Pengaruh Motivasi Kerja dan Kompensasi terhadap Produktivitas Kerja Pegawai pada Kantor Bawaslu Kota Bontang - Rohani, Auliya; Agustina, Agustina; Agusyani, Agusyani (Masyarakat Ekonomi Syariah Bogor, 2024)
This research was conducted to determine the influence of work motivation and compensation on employee work productivity at the Bawaslu Office in Bontang City. The respondents for this research were 57 employees who worked at the Bawaslu Office in Bontang City and the ranks of District Supervisors throughout Bontang City. The results of this research are: From the results of multiple linear regression analysis tabulated using SPSS, simultaneously there is a significant influence between work motivation and compensation on work productivity, and the partial test results (t test) and (f test) show that there is a good influence between work motivation and compensation, and shows that there is no influence between compensation and work productivity.